Effects of Extreme Weather Events on Internal Migration in Rural Guatemala - Sivisaca, Deicy Lozano [UNESP]; Robalino, Juan; Cascante, Adriana Chacón; Imbach, Pablo; Sandoval, Catalina (Wiley, 2021)
We estimate the effects of extreme weather events on internal migration in Guatemala between 1997 and 2002. Using data from rural municipalities, we implement a generalized linear model that deals with fractions as we explain migration between municipalities. We find that, on average, the presence of a drought in a municipality of origin significantly reduces migration, although, on average, extreme precipitation events increase migration significantly. These results were robust after controlling for several demographic, social, geographical, economic, and climatic variables from the municipalities of origin and destination, as well as extreme climatic events that occurred before the study period. We also organized the sample according to season (dry and rainy season), destination of migrants (rural and urban), level of precipitation (dry and rainy areas), and proximity of municipalities (neighbors or not). Results did not change. This evidence shows the importance of considering the type of weather events when thinking about their consequence on migration.